2018
DOI: 10.1039/c8tb01100a
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled proteinaceous wound dressings attenuate secondary trauma and improve wound healing in vivo

Abstract: Stimuli-responsive gauze coated with a phase-transitioned lysozyme nanofilm (PTLF@gauze) has been developed, which exhibits great potential for clinical applications by reducing secondary trauma and relieving the pain of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 59 publications
0
51
0
Order By: Relevance
“…At present, most medical dressings still use traditional cotton gauze. Nevertheless, traditional cotton gauze needs to be replaced frequently, and easily adheres to the wound, which can easily lead to secondary tissue trauma and bacterial breeding [4,5,6]. Moreover, huge dressing wastes cause great harm to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…At present, most medical dressings still use traditional cotton gauze. Nevertheless, traditional cotton gauze needs to be replaced frequently, and easily adheres to the wound, which can easily lead to secondary tissue trauma and bacterial breeding [4,5,6]. Moreover, huge dressing wastes cause great harm to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, the disulfide bonds of native lysozyme were reduced efficiently by TCEP, [ 24 ] and then a PTL/C‐AMG nanofilm was formed on the silicon wafer surface, which was actually composed of densely packed oligomeric nanoparticles with an average diameter of 50 nm, as revealed by AFM and transmission electron microscopy (TEM; Figure 1b,c and Figure S4, Supporting Information), similar to the oligomeric nanoparticles structures of the pure PTL film reported previously. [ 24,26,29,30 ] The PTL/C‐AMG film thickness could be regulated from 3 to 42 nm by changing the incubation time from 1 to 50 min (Figure S5, Supporting Information), and such film on the silicon surface did not show obvious changes in surface topography after being subjected to various harsh conditions, such as extreme pH (2, 11), salt solution, high temperature, organic solvents, and adhesive tape peeling (Figure S6, Supporting Information). Similar to that of amelogenin‐forming amyloid structures, [ 10,11 ] the amyloid‐like structure of the PTL/C‐AMG nanofilm was identified by circular dichroism (CD) and Fourier transform infrared (FTIR) spectra, which showed an increase in the characteristic β‐sheet structure (218 nm in CD and 1625 cm −1 in FTIR) (Figure 1d,e).…”
Section: Methodsmentioning
confidence: 99%
“…Zhao et al found the PTLF could be degraded and detached from the substrate surface in the presence of vitamin C. [ 119 ] Later, Li et al designed an on‐demand degradable boron carrier based on this feature of PTLF to treat triple‐negative breast cancer (Figure 10b). [ 120 ] Boron nitride nanoparticles (BNNPs) were coated by a PTLF, which could protect them from hydrolysis to prolong blood circulation.…”
Section: Biomedical Applicationsmentioning
confidence: 99%